Does digital media use increase risk of social-emotional delay for Chinese preschoolers?. Issue 1 (2nd January 2023) - Gou, He; Perceval, Garon
ABSTRACT: Many studies have shown a relationship between preschool-aged children's digital media use and their cognitive and physical development. However, the relationship between preschoolers' digital media exposure and social-emotional development is under-researched both in and outside of China. The current study explores associations between both the amount and content of digital media, as well as parental mediation and other demographic variables, and Chinese preschoolers' risk of social-emotional delay. Nine hundred and forty-four parents of preschoolers aged 42 to 72 months completed the Ages and Stages Questionnaire: Social-Emotional II (ASQ: SE II) and a media diary. Results indicate that time spent on digital media is positively associated with preschool-aged children's risk of social-emotional delay, particularly for children from affluent families. Children were less likely to be at risk with increased restrictive mediation while more likely to be at risk when parental co-use increased. We did not find a relationship between digital content type and social-emotional development, which may due to our focus on the interactive conditions of the content rather than the social-emotional lessons in the content. The present study suggests possible predictors of preschoolers' social-emotional delay related to digital media usage and parental mediation. IMPACT SUMMARY: Prior State of Knowledge : Recent studies have shown associations between inappropriate digital media use and children's social-emotional problems such as interpersonal skills, emotional understanding, and self-regulation. Novel Contributions : This large scale study is the first to reveal a positive relationship between increased digital media time and preschoolers' social-emotional delay within a Chinese cultural context, which additionally identifies affluent families as an at-risk population. Practical Implications : These findings provide valuable insights for parents implementing evidence-based parental mediation strategies for children's digital media use with a consideration toward social-economic status and cultural background. These exploratory findings also inform the direction of future studies investigating such evidence-based strategies.